Dendrobium tuensangense, a new species of Orchidaceae from Nagaland, Northeast India - Odyuo, Nripemo; Deori, Chaya; Daimary, Ranjit (Phytotaxa, 2017)
Dendrobium tuensangense N. Odyuo & C. Deori (Orchidaceae), a new species from Tuensang district of Nagaland, Northeast India is described and illustrated. The new species is similar to D. dantaniense Guillaumin but differs in having uniformly elongate, slender stems, floral bracts ovate to elliptic acuminate, obtuse, shorter than the ovary and pedicel; sepals and petals pale cream coloured; side lobes papillose on dorsal and ventral side, papillae purplish, fan shaped, very broad, apex obtuse, margin erose; midlobe apex narrower, 1 mm broad; anther head with an acute projection of 0.5 mm long. It is also similar to Dendrobium bicameratum Lindl. but differs in having uniformly elongate, slender stems, an acute projection of 0.5 mm long on the anther head, sepals and petals pale cream coloured; side lobes papillose on dorsal and ventral side, papillae purplish, fan shaped, very broad, obtuse, margin erose.